Объяснение:
Записать в стандартном виде
400000 = 4*10^5
23000 = 2,3*10^4
8760000 = 8,76*10^6
1230 = 1,23*10^3
43 = 4,3*10^1
0,00008 = 8*10^-5
0,0076 = 7,6*10^-3
0,098 = 9,8*10^-2
0,54 = 5,4*10^-1
0,1 = 1*10^-1
7000000 = 7*10^6
560000 = 5,6*10^5
2130000 = 2,13*10^6
19700 = 1,97*10^4
51 = 5,1*10^1
0,0007 = 7*10^-4
0,00678 = 6,78*10^-3
0,042 = 4,2*10^-2
0,34 = 3,4*10^-1
0,9 = 9*10^-1
Записать в виде натурального числа или десятичной дроби:
5 ∙ 106 = 5000000
2,7 ∙ 103 = 2700
1,56 ∙ 104 = 15600
6,78 ∙ 102 = 678
3 ∙ 10-6 = 0,000003
1,2 ∙ 10-4 = 0,00012
4,76 ∙ 10-3 = 0,00476
2,3 ∙ 10-1 = 0,23
2 ∙ 105 = 200000
7,7 ∙ 104 = 77000
5,86 ∙ 105 = 586000
2,18 ∙ 103 = 2180
4 ∙ 10-5 = 0,00004
7,2 ∙ 10-5 = 0,000072
6,12 ∙ 10-2 = 0,0612
6,5 ∙ 10-1 = 0,65
1) (a+b)² (a-b) - 2ab(b-a) - 6ab(a-b) =(a -b)³ .
(a+b)² (a-b) - 2ab(b-a) - 6ab(a-b) =(a-b)( ( a+b)² +2ab - 6ab ) =
(a-b)(a² +2ab +b² +2ab -6ab) =(a-b)(a² -2ab +b² ) =(a-b)(a -b)² =(a -b)³ .
---
2) (a² +b²)(a⁴ - a²b² +b⁴) +(a³ -b³)(a³ +b³ ) =2a⁶.
(a² +b²)(a⁴ - a²b² +b⁴) +(a³ -b³)(a³ +b³ ) = (a²)³ +(b²)³ +(a³)² -(b³)² =
(a²)³ +(b²)³ +(a³)² - (b³)² =a⁶ +b⁶ + a⁶ - b⁶ =2a⁶.
---
3) (a²+b²)(c²+d²)= (ac+bd)²+(ad-bc)² .
(a²+b²)(c²+d²) =a²c² +a²d² + b²c² + b²d² =
(a²c² +2*ac*bd+ b²d²) +(a²d² - 2*ad*bc+ b²c² ) = (ac+bd)²+(ad-bc)² .
---
4) (a²+cb²)(d²+ce²) = (ad+cbe)²+c(ae - bd)² .
(a²+cb²)(d²+ce²) =a²d² +a²ce² + cb²d² +c²b²e² =(a²d² +c²b²e²) +c(a²e² + b²d²) =
(a²d² + 2*ad*cbe+c²b²e²) +c(a²e² - 2ae*bd+ b²d²) = (ad+cbe)²+c(ae - bd)².